The Lion of Petra - Mundy, Talbot, 1879-1940 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Lion of Petra" by Talbot Mundy is a historical adventure novel likely written in the early 20th century. The narrative revolves around a desert adventure filled with intrigue, cunning, and encounters with various characters and factions, primarily focusing on the infamous Ali Higg, the self-proclaimed Lion of Petra. The central characters include Grim, a determined and resourceful American, and the young narrator, who joins Grim on a journey to confront the notorious sheikh in the desert. The opening portion introduces the background of the protagonist and sets the stage for the adventure, highlighting the vibrant desert landscape and the eclectic mix of characters. As the narrator settles into Grim$1 (Bs makeshift military boarding house in Jerusalem, he becomes acquainted with the ins and outs of desert life through the preparation of an expedition. Grim's allure to adventure and the cultural dynamics between the Westerners and the Arabs create an atmosphere ripe for conflict, suspense, and veiled threats, all leading up to the impending journey to Petra and the encounter with Ali Higg, where clashes of ambition and power loom over the horizon. (This is an automatically generated summary.)s
Release date is 2006-09-17
Produced by Mark R. Jaqua
Keywords: Middle East -- Fiction